STABILITY ANALYSIS TO ASCERTAIN THE PERFORMANCE OF DIFFERENT GENOTYPES OF WHEAT [TRITICUM AESTIVUM L.] - B. S. JAT, B. R. RANWAH, BAUDH BHARTI A. K. PARIHAR (The Bioscan, 2015)
The current study aimed at ascertaining the performance of bread wheat genotypes under different environmental conditions. The stability parameters were estimated for yield and its contributing trait which exhibited homoge- neous error mean square in different environments. The mean squares due to genotypes, E + (G x E), G x E and pool deviation were significant for the studied characters. This suggesting differential response of the genotypes and need to stability analysis. Results revealed that two genotypes PBW 373 and Raj 3765 had non- significant deviation from regression (S2di) for grain yield per plant. Furthermore, three crosses viz., HD 2687 x Raj 3077, DBW 17 x PBW 373 and PBW 373 x Raj 4037 showed high per se performance with below average response (bi > 1) which indicating suitability for favourable environment. Hence, above mentioned genotypes and crosses could be used to accelerate wheat improvement programmes for different cropping system